Long-term pioglitazone treatment enhances lipolysis in rat adipose tissue - Pravenec, M; Kazdová, L; Maxová, M; Zídek, V; Mlejnek, P; Simáková, M; Kurtz, T W (International journal of obesity (2005), 2008)
OBJECTIVES: The insulin-sensitizing effects of thiazolidinediones are believed to depend at least in part on reductions in circulating levels of nonesterified fatty acids (NEFA). The mechanisms that mediate the reductions in NEFA are not fully understood and could involve reductions in adipose tissue lipolysis, increases in glyceroneogenesis and NEFA reesterification in triglycerides in adipose tissue and increases in NEFA metabolism by oxidative tissues. METHODS: In a congenic strain of spontaneously hypertensive rats that fed a high-sucrose diet to promote features of the metabolic syndrome, we studied the effects of chronic pioglitazone treatment over 4 months on adipose tissue lipolysis and NEFA metabolism. RESULTS: We observed significant increases in basal and adrenaline-stimulated NEFA and glycerol release, and near-total suppression of NEFA reesterification in epididymal adipose tissue isolated from rats chronically treated with pioglitazone. However, pioglitazone-treated rats also exhibited significant increases in mitochondrial DNA levels in adipose tissue (3.2-fold increase, P=0.001) and potentially greater sensitivity to the antilipolytic effects of insulin than untreated controls. In addition, chronic pioglitazone treatment was associated with increased palmitate oxidation in soleus muscle, reduced fasting levels of serum NEFA and triglycerides, as well as reduced serum levels of insulin and increased serum levels of adiponectin. CONCLUSIONS: Despite suppressing NEFA reesterification and increasing basal and adrenaline-stimulated lipolysis, chronic pioglitazone treatment may decrease circulating NEFA levels in part by increasing adipose tissue sensitivity to the antilipolytic effects of insulin and by enhancing NEFA oxidation in skeletal muscle.
Keywords: potkani inbrední SHR; tuková tkáň; lipolýza; Glycerol; Thiazolidinediones; thiazolidindiony; Fatty Acids, Nonesterified; mitochondriální DNA; Adiponectin; Rats; glycerol; Hypoglycemic Agents; Palmitates; triglyceridy; adiponektin; Lipolysis; inzulin; Animals; pioglitazon; DNA, Mitochondrial; Triglycerides; palmitany; Rats, Inbred SHR; kyseliny mastné neesterifikované; zvířata; Pioglitazone; krysa rodu Rattus; kosterní svaly; hypoglykemika; Muscle, Skeletal; Adipose Tissue; Insulin